Lower extremity osteoarthritis: optimising musculoskeletal health is a growing global concern: a narrative review. Issue 13 (20th July 2018) - Leech, Richard D; Eyles, Jillian; Batt, Mark E; Hunter, David J
Abstract : The burden of non-communicable diseases, such as osteoarthritis (OA), continues to increase for individuals and society. Regrettably, in many instances, healthcare professionals fail to manage OA optimally. There is growing disparity between the strength of evidence supporting interventions for OA and the frequency of their use in practice. Physical activity and exercise, weight management and education are key management components supported by evidence yet lack appropriate implementation. Furthermore, a recognition that treatment earlier in the disease process may halt progression or reverse structural changes has not been translated into clinical practice. We have largely failed to put pathways and procedures in place that promote a proactive approach to facilitate better outcomes in OA. This paper aims to highlight areas of evidence-based practical management that could improve patient outcomes if used more effectively.